The combined effects of acidification and acute warming on the embryos of Pacific herring (Clupea pallasii) - Singh, Nicole R.; Love, Brooke; Murray, Christopher S.; Sobocinski, Kathryn L.; Cooper, W. James (Frontiers in Marine Science, 2023)
Anthropogenic climate change is projected to affect marine ecosystems by challenging the environmental tolerance of individuals. Marine fishes may be particularly vulnerable to emergent climate stressors during early life stages. Here we focus on embryos of Pacific herring (Clupea pallasii), an important forage fish species widely distributed across the North Pacific. Embryos were reared under a range of temperatures (10-16°C) crossed with two pCO2 levels (600 and 2000 μatm) to investigate effects on metabolism and survival. We further tested how elevated pCO2 affects critical thermal tolerance (CTmax) by challenging embryos to short-term temperature fluctuations. Experiments were repeated on embryos collected from winter and spring spawning populations to determine if spawning phenology corresponds with different limits of environmental tolerance in offspring. We found that embryos could withstand acute exposure to 20°C regardless of spawning population or incubation treatment, but that survival was greatly reduced after 2-3 hours at 25°C. We found that pCO2 had limited effects on CTmax. The survival of embryos reared under chronically warm conditions (12°, 14°, or 16°C) was significantly lower relative to 10°C treatments in both populations. Oxygen consumption rates (MO2) were also higher at elevated temperatures and pCO2 levels. However, heart contraction measurements made 48 hours after CTmax exposure revealed a greater increase in heart rate in embryos reared at 10°C compared to 16°C, suggesting acclimation at higher incubation temperatures. Our results indicate that Pacific herring are generally tolerant of pCO2 but are vulnerable to acute temperature stress. Importantly, spring-spawning embryos did not clearly exhibit a higher tolerance to heat stress compared to winter offspring.